International biological engagement programs facilitate Newcastle disease epidemiological studies - Patti J. Miller (Frontiers in Public Health, 2015)
Infections of poultry species with virulent strains of Newcastle disease virus (NDV) cause Newcastle disease (ND), one of the most economically significant and devastating diseases for poultry producers worldwide. Biological engagement programs (BEP) between the Southeast Poultry Research Laboratory (SEPRL) of the United States Department of Agriculture and laboratories from Russia, Pakistan, Ukraine, Kazakhstan and Indonesia collectively have produced a better understanding of the genetic diversity and evolution of the viruses responsible for ND, which is crucial for the control of the disease. The data from Kazakhstan, Russia and Ukraine identified possible migratory routes for birds that may carry both virulent NDV (vNDV) and NDV of low virulence into Europe. In addition, related NDV strains were isolated from wild birds in Ukraine and Nigeria, and from birds in continental USA, Alaska, Russia, and Japan, identifying wild birds as a possible mechanism of intercontinental spread of NDV of low virulence. More recently, the detection of new sub-genotypes of vNDV suggests that a new, fifth, panzootic of ND has already originated in Southeast Asia, extended to the Middle East, and is now entering into Eastern Europe. Despite expected challenges when multiple independent laboratories interact, many scientists from the collaborating countries have successfully been trained by SEPRL on molecular diagnostics, best laboratory practices, and critical biosecurity protocols, providing our partners the capacity to further train other employees and to identify locally the viruses that cause this OIE listed disease. These and other collaborations with partners in Mexico, Bulgaria, Israel, and Tanzania have allowed SEPRL scientists to engage in field studies, to elucidate more aspects of ND epidemiology in endemic countries, and to understand the challenges that the scientists and field veterinarians in these countries face on a daily basis. Finally, new viral characterization tools have been developed and are now available to the scientific community.